State of the art of research on modified asphalt mixtures in Colombia - Rondón Quintana, Hugo Alexander (2025)
In the world, the technology of modified asphalts has been a widely used technique to improve the characteristics that reveal the conventional asphalt mixtures when they are put at elevated levels of traffic and gradients of temperature. In Colombia, the research developments in the area of asphalts and de modified asphalt mixtures are extensive in comparison with the amount of constructed structures of flexible pavements using this technology. The article presents the state of the knowledge of the studies that have been developed with diverse groups and institutions of investigation in the modified area of asphalts and asphalt mixtures in Colombia.